Mathematics and the craft of thought in the Anglo-Dutch Renaissance - Chan, Eleanor (Material cultures of music), author.
1 online resource.
Keywords: "Geometry had a mercurial nature in the sixteenth century. Transmitted from antiquity in the form of Euclid's Elements, it was many years before geometry moved from the scholastic sphere and before its language and logic began to be used in an explicitly practical context. In 1570, Henry Billingsley translated Euclid's Elements into the English vernacular. In 1604, Jan Pieterszoon Dou followed suit and produced the first translation in the Dutch vernacular. These were both seminal moments in what is now known as the scientific revolution, but they were also part of a broader shift towards the establishment of geometry as a practical and analytical tool. Mathematics and the Craft of Thought in the Anglo-Dutch Renaissance sheds light on the remarkable culture shift that occurred around the turn of the seventeenth century, and on the geometrical imagination which followed. It shows how the visual language of early modern European geometry was constructed by borrowing and quoting from contemporary visual culture. Practical geometry in this period was built out of craft metaphors. The verbal and visual language of this form of mathematics, far from being simply immaterial, is designed to tantalize with material connotations"--